Domestic Violence against Women in Nigeria: Economic and Legal Dimensions - Mnyim, Mwuese Modupe; Gisaor, Vincent Iorja (ABUAD Law Journal, 2019)
Several reports reveal escalating levels of violence against women in Nigeria and around the world. This paper thus investigated domestic violence in Nigeria from the perspective of economic costs and legal instruments enacted to control the menace. The result confirms that domestic violence has severe economic cost in Nigeria ranging from cost of justice, health care services, social services, education, business and employment cost, to household and personal cost running into billions of naira. Various international and local legal instruments applicable in Nigeria have also been examined. However, the numerous gaps, inconsistent provisions and poor implementation of laws have denied women in Nigeria the protection the law can guarantee. The paper thus recommends the harmonization of all legislation related to domestic violence. All legislation be also amended to bring them in line with the human rights and gender equality requirements. Finally, Religious and traditional institutions should be co-opted to sensitize the people within their domain on the ills of violence particularly of this genre.